2013
DOI: 10.1109/tbme.2013.2244599
|View full text |Cite
|
Sign up to set email alerts
|

Grand Challenges in Bioengineered Nanorobotics for Cancer Therapy

Abstract: One of the grand challenges currently facing engineering, life sciences, and medicine is the development of fully functional nanorobots capable of sensing, decision making, and actuation. These nanorobots may aid in cancer therapy, site-specific drug delivery, circulating diagnostics, advanced surgery, and tissue repair. In this paper, we will discuss, from a bioinspired perspective, the challenges currently facing nanorobotics, including core design, propulsion and power generation, sensing, actuation, contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Since 1959 in the Nobel physicist Richard P. Feynman's prescient talk "There's plenty of room at the bottom", tiny nanorobots that could be designed, manufactured, and introduced into human body to perform cellular repairs at the molecular level have been imagined [26]. Currently, it is challenging to fabricate a nanorobot capable of performing even a simple medical task by traditional engineering method [27], but biological nanomaterials can be used to construct complex "machinery" capable of actuation, propulsion, sensing, computation, and decision making [28]. In 2012, Douglas et al [29] used DNA molecules to create a nanorobot (35 nm × 35 nm × 45 nm) which can deliver drugs to target cancer cells and the results showed that nanorobots can induce a variety of tunable changes in cell behavior, practically opening the door to nanorobotic medicine, such as killing cancer cell, cleaning clogged arteries, repairing tissues, and crushing stones that form inside organs [30].…”
Section: Blueprint Of Micro/nano Automation In Personalized Cancementioning
confidence: 99%
“…Since 1959 in the Nobel physicist Richard P. Feynman's prescient talk "There's plenty of room at the bottom", tiny nanorobots that could be designed, manufactured, and introduced into human body to perform cellular repairs at the molecular level have been imagined [26]. Currently, it is challenging to fabricate a nanorobot capable of performing even a simple medical task by traditional engineering method [27], but biological nanomaterials can be used to construct complex "machinery" capable of actuation, propulsion, sensing, computation, and decision making [28]. In 2012, Douglas et al [29] used DNA molecules to create a nanorobot (35 nm × 35 nm × 45 nm) which can deliver drugs to target cancer cells and the results showed that nanorobots can induce a variety of tunable changes in cell behavior, practically opening the door to nanorobotic medicine, such as killing cancer cell, cleaning clogged arteries, repairing tissues, and crushing stones that form inside organs [30].…”
Section: Blueprint Of Micro/nano Automation In Personalized Cancementioning
confidence: 99%
“…We refer to these nanomotes as 'nanocollectors'. Nanocollectors can be attached to the cell walls by using some bioengineering techniques such as atomic force microscopy or some form of artificial bacteria [9]. Each nanocollector has been equipped with a nanoscale energy harvester [5] to harvest energy from pressure variation and cell wall movement during the respiration cycle ; a nanosensor [16] to measure the target markers in the exchanged gases; a nanomemory [13] to save the detected marker; a nanoprocessor [4] to run the required algorithm and a nanotransmitter [7] to transfer the recorded markers wirelessly to a nanoscale remote station.…”
Section: Proposed Architecturementioning
confidence: 99%
“…Medical micro-/nano-robots are another hot research topic [39,43,215,284,294,389], inspired by the science fiction movie Fantastic Voyage, which miniaturized submarine entering a human body to perform life-saving surgery. The proposed applications include treating tumors that cannot be accessed via traditional surgery, removing fatty deposits from the walls of arteries, breaking blood clots into smaller pieces, removing stones in the liver and kidney, delivering a payload of an adhesive to damaged sites of cranial artery, repairing detached retina, delivering drugs to specific locations, and in situ sensing and diagnostics [39].…”
Section: Biomedicinementioning
confidence: 99%
“…The proposed applications include treating tumors that cannot be accessed via traditional surgery, removing fatty deposits from the walls of arteries, breaking blood clots into smaller pieces, removing stones in the liver and kidney, delivering a payload of an adhesive to damaged sites of cranial artery, repairing detached retina, delivering drugs to specific locations, and in situ sensing and diagnostics [39]. The critical design considerations include core, propulsion (to move it around), power, sensing and actuation, decision making, integration, insertion, and removal [39,215]. Nanoparticles are often used for various purposes [92,215,458].…”
Section: Biomedicinementioning
confidence: 99%